The creative Labor of Augusto Rodrigues in the Creation of the Little Art Schools of Brazil and the Art & Education Newspaper (Revista Educação, Artes e Inclusão, 2022)
The first Escolinha de Arte do Brasil – EAB (Little Art School of Brazil) and the newspaper Arte & Educação (Art & Education) represent the “creative labor” of Augusto Rodrigues, scholars, artists and teachers. All of whom transformed the school and the newspaper in a space of information and development in the field of education through art during the second half of the 20th century. The objective is to understand this developmental and “creative labor”, as well as the artistic, educational and cultural legacy of this period. The methodology consisted of bibliographic investigation, in line with Gil (2002), in addition to a source of periodical catalogs around the work of Jucá (2003). The theoretical framework of this analysis is supported by the following authors: Herbert Read (1986, 2007); Dewey (2010); Barbosa (2015); Bachelard (2003); Britto and Palma (2019); Miranda (2009), among others. The research reached the following conclusions: Augusto Rodrigues has influenced a whole generation of art educators in Brazil and other countries that have had knowledge of his life, opus and labor. The Art & Education was one of the first periodicals to spread ideas not only of education through art but also of other developmental and expressive contexts.
Keywords: Little Art School; Augusto Rodrigues; Art and Education